Because Your Grandparents Love You - Clements, Andrew 1949-; Alley, R. W. 1955- (Boston : Clarion Books, Houghton Mifflin Harcourt, 2015)
Grandparents are the reassuring heroes in this story about a boy and girl who go on an overnight visit at their grandmother and grandfather's farm.
Keywords: Grandparents -- Juvenile fiction; Farm life -- Juvenile fiction; Grandparents -- Fiction; Farm life -- Fiction